2019
DOI: 10.1029/2019gl085031
|View full text |Cite
|
Sign up to set email alerts
|

Convective Precipitation Efficiency Observed in the Tropics

Abstract: Precipitation efficiency refers to the fraction of condensate in the atmosphere that reaches the surface as precipitation. A high‐quality data set of radar‐estimated precipitation rates and convective scale vertical velocity near Darwin, Australia, is used to construct the first estimate of precipitation efficiency at convective scales for a long record of observations in the tropics. It is found that precipitation efficiency increases with precipitation rate and midtropospheric humidity and decreases with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
(69 reference statements)
0
22
0
Order By: Relevance
“…Changes in precipitation efficiency are also closely related to changes in cloud microphysics, changes in entrainment, and convection dynamics. A study on precipitation efficiency at convective scales for a long record of observations in the tropics 143 found that precipitation efficiency increases with precipitation rate and mid-tropospheric humidity and decreases with increasing CAPE and surface temperature. However, these efficiency differences do not directly translate to changes in precipitation intensity due to compensating changes in cloud updraft velocities 143 .…”
Section: Cloud-scale Dynamics and Microphysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in precipitation efficiency are also closely related to changes in cloud microphysics, changes in entrainment, and convection dynamics. A study on precipitation efficiency at convective scales for a long record of observations in the tropics 143 found that precipitation efficiency increases with precipitation rate and mid-tropospheric humidity and decreases with increasing CAPE and surface temperature. However, these efficiency differences do not directly translate to changes in precipitation intensity due to compensating changes in cloud updraft velocities 143 .…”
Section: Cloud-scale Dynamics and Microphysicsmentioning
confidence: 99%
“…A study on precipitation efficiency at convective scales for a long record of observations in the tropics 143 found that precipitation efficiency increases with precipitation rate and mid-tropospheric humidity and decreases with increasing CAPE and surface temperature. However, these efficiency differences do not directly translate to changes in precipitation intensity due to compensating changes in cloud updraft velocities 143 . Climate change effects of precipitation efficiency are uncertain, with changes in efficiency found at different temperatures 142 and some evidence of increases in efficiency with warming in small domains, although this is complicated by changes to convective organisation 144 .…”
Section: Cloud-scale Dynamics and Microphysicsmentioning
confidence: 99%
“…The low‐troposphere represents the moisture intake thickness of the cloud and the evaporation region of raindrops after leaving the cloud. High low‐tropospheric relative humidity promotes moisture supply to the cloud and restricts the evaporation of raindrops, thus it is beneficial for increasing the PE (Market et al ., 2003; Narsey et al ., 2019). It is thought that the strong vertical wind shear in the mid‐troposphere causes the cloud to tilt, which increases the contact and entrainment between the cloud and the environmental dry air, resulting in an increased probability of hydrometeors evaporating, thereby reducing the PE of the cloud (Market et al ., 2003; Zhou, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, while we have largely tried to focus on the potential influence that changes in dynamics due to changing convective organization could have on extreme precipitation, microphysics may play also play an important role. Compensation between microphysics and dynamics has been identified in observations [60] and with changes in organization in model simulations [39•]. Simulated scaling of extreme precipitation with warming can vary with how microphysics is represented [61].…”
Section: Discussionmentioning
confidence: 99%